Transformasi Layanan Keuangan Syariah di Era Digitalisasi - Rika Rika; Abustan Nur; Akbar M.Sunusi; Amanda Julianti; Nurul Waqia; Eki Pratiwi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The digital era has brought fundamental changes to the Islamic banking industry, particularly in marketing management and financial service delivery. The digitalization of financial services enables Islamic banks to enhance operational efficiency, expand market reach, and improve customer experience. This study adopts a qualitative approach using a literature review method by analyzing relevant academic journals, books, and national scientific publications related to digital transformation and Islamic banking marketing. The findings indicate that digital transformation in Islamic banking requires not only technological innovation but also strategic digital marketing, enhancement of customer financial literacy, strengthening customer trust, and consistent integration of Sharia principles in digital services. The consistency of Sharia values in digital marketing strategies plays a crucial role in differentiating Islamic banks from conventional financial institutions and in building sustainable customer loyalty. Therefore, digital transformation becomes a strategic instrument for Islamic banks to strengthen competitiveness and promote inclusive and ethical financial services in the digital era